Intrinsic and Wind-Driven Decadal Variability of the Kuroshio Extension in Altimeter Observations - Zhou, Guidi; Li, Zhuhua; Cheng, Xuhua (Frontiers in Marine Science, 2021)
In this work we use satellite altimeter observations to study the mechanism of decadal variability of the Kuroshio Extension (KE), with special attention on jet-eddy energy transfer, and on the relationship between the wind-driven and oceanic intrinsic sea surface height anoma-lies (SSHAs). It is shown that energy feedback between the jet and mesoscale eddies can main-tain the decadal oscillation of the KE. The wind-driven SSHAs are broad-scale and very weak compared to the intrinsic variability, but can potentially drive delayed responses of the latter by modulating vorticity advection from upstream. KE perturbations resulting from the intrinsic vari-ability, on the other hand, could feedback onto the wind-driven SSHAs by inducing anomalous basin-scale wind stress. The KE jet is thus an integrate system involving the jet and the eddies, paced by and feeding back to wind stress anomalies.